Asprothrips bimaculatus sp.n. (Thripidae, Dendrothripinae) - Michel, Bruno; Ryckewaert, Philippe (Zootaxa, 2014)
According to the International Code of Zoological Nomenclature Article 16.4.2 the description of a new species must be accompanied by a statement of intent that the holotype will be deposited in a collection and a statement indicating the name and location of that collection. Unfortunately this requirement of the Code was not complied with in our recent Zootaxa paper (Michel & Ryckewaert 2014). This brief note is to rectify the situation, and to make the name available.